Effect of Gum Tragacanth-Sodium Alginate Active Coatings Incorporated With Epigallocatechin Gallate and Lysozyme on the Quality of Large Yellow Croaker at Superchilling Condition - Pei, Juxin; Mei, Jun; Yu, Huijie; Qiu, Weiqiang; Xie, Jing (Frontiers in Nutrition, 2022)
This research was to investigate the synergistic interactions of gum tragacanth (GT) - sodium alginate (SA) active coatings incorporated with epigallocatechin gallate and lysozyme on the quality of large yellow croaker (Larimichthys crocea) during superchilling storage at -3 °C. Results indicated that GT-SA active coatings containing epigallocatechin gallate (EGCG) and lysozyme (LYS) were effective in reducing total viable count (TVC), psychrophilic bacteria and Pseudomonas spp., and lowering the formations of off-odour compounds such as total volatile basic nitrogen (TVB-N), malondialdehyde (MDA) and off-favour amino acid (histidine). The spme gas chromatography-mass spectrometer (SPME-GC/MS) was applied to characterize and quantify volatiles compounds of large yellow croaker samples during superchilling storage and the relative content of fishy flavor compounds (including 1-octen-3-ol and acetoin) was significantly reduced in the active coatings treated samples. Furthermore, the GT-SA active coatings containing EGCG and LYS treatments was found to be more effective in retarding the migration of water based on magnetic resonance imaging (MRI) results, and in maintaining the organoleptic quality of large yellow croaker superchilling storage at -3 oC according to sensory evaluation results. The results showed that GT-SA active coatings containing EGCG and LYS was effective to be used as a fish preservative to improve the quality and prolong the shelf life of large yellow croaker superchilling storage.